Assessing Quality of Life, Menopausal Symptoms, and Coping Strategies among Menopausal Women: A Cross-Sectional Study in Cumilla, Bangladesh (Central Medical College Journal, 2024)
Background: Menopause is a natural biological transition that can significantly impact a woman's quality of life due to associated physiological, psychological, and social changes. In Bangladesh, there is a lack of awareness and understanding about menopause and its health implications. This study aimed to assess the health-related quality of life, prevalence of menopausal symptoms, coping mechanisms, and associated socio-demographic factors among menopausal women in the South Sadar region of Cumilla, Bangladesh. Methods: This cross-sectional, quantitative study was conducted at the Central Medical College & Hospital in Cumilla from October 2023 to March 2024. The sample included 400 women aged 40-59 years who had experienced natural menopause at least one year prior. Data was collected through face-to-face interviews using a structured questionnaire, the Menopausal Rating Scale (MRS) for assessing quality of life and symptom severity, and a coping mechanisms checklist. Descriptive statistics, chi-square, and Fisher's exact tests were used for data analysis. Results: This community-based study included 400 postmenopausal women aged between 40-59 years (mean 53.51 ± 3.43 years). The prevalence of menopausal symptoms based on the Menopausal Rating Scale (MRS) was high, with 75.5% experiencing somatic symptoms, 69.8% psychological symptoms, and 49.3% urogenital symptoms. The most common symptoms were joint/muscular discomfort (60.3%), anxiety (50.8%), and bladder problems (35.3%). The mean total MRS score of 9.5 ± 5.3 indicated a moderate-to-severe symptom burden. A staggering 70.25% of women had poor quality of life related to menopausal symptoms. Factors significantly associated with poor quality of life included rural residence (p=0.014), lower education (p